Religious and moral education - McGlinchey, Mariela (Hodder Gibson, 2021)
Syllabus: CfE (Curriculum for Excellence, from Education Scotland) Level: BGE S1-3: Third and Fourth Levels Subject: RME Modernise and refresh RME. Topics such as social media, gender identity and artificial intelligence are explored alongside world religions, as pupils think critically about our rapidly changing world. Covering all CfE Third and Fourth Level Benchmarks (plus some key content for Second Level), this ready-made and differentiated course puts progression for every pupil at the heart of your curriculum. > Ask questions and solve problems: 'Thinking skills' for later life are developed through sensitive, scaffolded consideration of Judaism, Christianity, Islam, Buddhism, Humanism and diverse and inclusive morality and belief topics that will capture every pupil's interest > Personalise the learning process: Each chapter contains learning intentions, starter tasks, explanations and activities (with accompanying success criteria) that you can deliver across one or two lessons, choosing the appropriate depth and pace for your pupils > Meet the needs of each pupil in your class: The content and activities are designed to ensure accessibility for those with low prior attainment, while 'Challenge' tasks will stretch high achieving pupils > Effectively check and assess progress: Activities that can be used for summative and formative assessment, 'progress check' questions, and suggestions for gathering a portfolio of evidence help you to monitor progression against the Experiences & Outcomes and Benchmarks > Lay firm foundations for National qualifications: The skills, knowledge and understanding established through the course will set up pupils for success in National 5 RMPS > Deliver the 'responsibility for all' Es and Os: Plenty of activities that address literacy, numeracy and health and wellbeing skills are threaded through the book.